2018
DOI: 10.1016/j.appet.2018.06.032
|View full text |Cite
|
Sign up to set email alerts
|

Less is more: Negative income shock increases immediate preference in cross commodity discounting and food demand

Abstract: Negative income shock, or the rapid reduction in financial stability, has previously been shown to increase impulsive choice for money and demand for fast food. The interplay of these conditions for obesity is called reinforcer pathology. The present work examines the impact of negative income shock on monetary and fast food discounting using a cross-commodity delay discounting task and on purchasing of fast food and an alternative commodity. An obese sample (n=120) was recruited from Amazon Mechanical Turk an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
46
5

Year Published

2018
2018
2021
2021

Publication Types

Select...
4
2
2

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(53 citation statements)
references
References 40 publications
(60 reference statements)
2
46
5
Order By: Relevance
“…For example, income loss has been associated with a shift toward consumption of less healthy foods, eg, foods that are more energy dense and yield more calories for a given price. 30,31 Income drops may also result in loss of health insurance coverage, 32 although we did not observe that in this study population. Large drops in income may also lead to financial stress and worry, which are in turn linked to stresscoping behaviors such as increased intensity of cigarette smoking and alcohol use.…”
Section: Discussioncontrasting
confidence: 57%
“…For example, income loss has been associated with a shift toward consumption of less healthy foods, eg, foods that are more energy dense and yield more calories for a given price. 30,31 Income drops may also result in loss of health insurance coverage, 32 although we did not observe that in this study population. Large drops in income may also lead to financial stress and worry, which are in turn linked to stresscoping behaviors such as increased intensity of cigarette smoking and alcohol use.…”
Section: Discussioncontrasting
confidence: 57%
“…This is because the decisive significance of these technologies may dominate the reasonable and rational human decisions which, subordinated to algorithmically worked out solutions for emerging processes, may negatively affect the environment and lead to the tendency, not fully recognized yet, according to which masses of human beings would be subordinated to a small group of people ruling over them through algorithmic knowledge enhanced by the power of artificial intelligence and biotechnology. It is observed by many authors (Harari, 2017, Mellis et al, 2018, among others. In their works, they look at the past of the human species and assess their future while trying to outline the possible paths of change in the near future.…”
Section: Results and Discussion -Globalization Processes In Endogenoumentioning
confidence: 69%
“…Note, that we tested temporal discounting in the domain of finance. Future studies are needed to examine whether similar results are observed for temporal choices in other domains such as food or other consumables (Mellis et al, 2018).…”
Section: Discussionmentioning
confidence: 75%